Efektivitas Terapi Bermain pada Anak Usia Dini dengan Tantrum Akibat Ketergantungan Gadget - Nur Syamsia; Fredy Akbar K; Syamsidar Syamsidar (Jurnal Pengabdian Masyarakat JUPEMANDO, 2026)
This community service program aimed to reduce tantrum behavior in early childhood children who were dependent on gadget use. A total of 20 children aged 4–6 years in Polewali Mandar Regency participated in this program. The intervention was conducted through play therapy over a three-week period, with a frequency of two sessions per week, resulting in a total of six sessions. The activities included coloring, role-playing, ball games, and making and flying paper planes. Observational results showed that prior to the intervention, the frequency of tantrums ranged from 2–3 times per day with a duration of 6–10 minutes. After the intervention, the frequency decreased to 0–1 times per day with a duration of 1–3 minutes. In addition, the children demonstrated improvements in focus, emotional regulation, and social interaction with their surroundings. This program indicates that play therapy is an effective, simple, and enjoyable strategy for reducing tantrum behavior in early childhood related to gadget use.